Association of non-diabetic hyperglycemia with autonomic shift in acute ischaemic stroke - Sykora, Marek; Diedler, Jennifer; Poli, Sven; Rizos, Timolaos; Kellert, Lars; Steiner, Thorsten (European journal of neurology, 2012)
Background and purpose: The etiology of hyperglycemia in acute stroke remains controversial. It is unclear whether hyperglycemia arises as an epiphenomenon of stroke or as a reflection of underlying diabetes. Autonomic shift to sympathetic overactivity has been repeatedly observed in acute stroke. We hypothesize that hyperglycemia in acute stroke relates to autonomic imbalance and that the respective deleterious effects on stroke outcome may be cross-linked. Methods: A total of 75 non-diabetic patients with ischaemic stroke were included in a prospective study. Glucose levels at admission, fasting glucose, and glucose profiles were recorded. Autonomic function was quantified by the assessment of spontaneous baroreflex sensitivity (BRS) using a cross-correlation method. Demographic and clinical data including stroke volumes and admission National Institute of Heath Stroke Scale scores were included into the analysis. Functional outcome at 90 days was assessed using the modified Rankin Scale. Results: Hyperglycemia was correlated with decreased BRS independent of stroke severity or volume (r = −0.46, P < 0.001). In two separate regression models, glucose levels and BRS independently predicted unfavorable outcome at 3 months (OR = 1.06, CI = 1.02-1.11, P = 0.004 and OR = 0.75, CI = 0.56-0.99, P = 0.04). However, combining the models, only glucose levels (OR = 1.06, CI = 1.02-1.11, P = 0.004) remained independent predictor of outcome at 3 months. Conclusions: We observed an association between hyperglycemia and decreased BRS in non-diabetic patients, suggesting that hyperglycemic reaction in acute stroke may reflect stroke-related autonomic changes. Moreover, outcome effects of autonomic changes and hyperglycemia seem to be interdependent, putatively having the sympatho-vagal imbalance as common underlying mechanism. The possible therapeutic relevance of this finding warrants further studies.
First published: 25 May 2011
Gesehen am 21.06.2018